DESIGNING AN EFFECTIVE ORGANIZATIONAL STRUCTURE TO ACHIEVE PUBLIC ORGANIZATION OBJECTIVE (CASE STUDY IN PT. PTPN VII LAMPUNG) - Devi Yulianti; Dedy Hermawan (Spirit Publik: Jurnal Administrasi Publik, 2015)
This research is about the design of organization structure to create the effective public organization which is located in PT. Perkebunan Nusantara VII (Persero) Lampung.  This research is aimed to describe and analyze the relation between the design of organization structure of PTPN VII (Persero) with the company goals in creating the effective corporation. This study used qualitative approach with descriptive method.  The data was collected using documentation tehcnique and the data analysis was using reduction and conclusion technique. The results of this research were three main points. First, PTPN VII (Persero) has used the divisional structure.  Second, there were some alterations in divisional structure each year from 2008 until 2012. Third, the divisional structure of PTPN VII (Persero) hasn’t been able to support the achievement of company goals so that this corporation is no yet effective. The conclusion of this research is that the design of organization structure of PTPN VII (Persero) is not effective to reach the company goals. Keywords: organization, organization structure, and organization effectiveness.